Produktifitas Broiler yang Diberikan Ekstrak Kulit Manggis dan Ekstrak Daun Sirsak Via Air Minum - G G Maradon; I K Habsari; D T Marya (Politeknik Negeri Lampung, 2023)
Broiler are chickens that are genetically developed to achieve high body weight gain quickly. Rapid growth requires feed that has the right nutritional content to meet and support broiler chickens. This research aims to evaluate supplements from soursop leaf extract and mangosteen peel extract in broiler activity. This study used Complete Randomized Design (CRD) 5x4, namely 5 types of treatment and 4 replications. P0 = without the addition of soursop leaf extract and mangosteen peel extract; P1 = addition of 2 mg/KgBW soursop leaf extract + 2 mg/KgBW mangosteen peel extract; P2 = addition of 4 mg/KgBW soursop leaf extract + 4 mg/KgBW mangosteen peel extract; P3 = Addition of 6 mg/KgBW soursop leaf extract + 6 mg/KgBW mangosteen peel; P4= Addition of 8 mg/KgBW soursop leaf extract + 4 mg/KgBW mangosteen peel. The observed variables included consumption of broiler, body weight gain, feed consumption ratio, and mortality. The results showed that the addition of mangosteen peel extract and soursop leaf extract at a level of 2 mg/KgBW was able to increase body weight gain and reduce feed conversion